My first butterflies - Fitzsimons, Cecilia; Marshall, Ray (New York, N.Y., U.S.A. : Harper & Row, 1985)
Pop-up pictures introduce many kinds of butterflies and explanatory text discusses where they can be found.
Cover title.
Keywords: Butterflies; Toy and movable books; Butterflies; Toy and movable books